KAJIAN BENTUK DAN SIMBOL KUJANG SUNDA - Hendri Saifulhayat (Universitas Komputer Indonesia, 2018)
Kujang is known and considered as a weapon tradition that represents Sundanese society culture. Looking back, that a knife is the development of a sharp-sided discovery made up of rocky chunks of kalcedon that make humans rank first in the food chain on the face of the earth. The knife transforms into a long sword, thrown into a spear, jagged into a saw, squeezed with axis into scissors and many other more specific functions into a variety of tools because of the growing demands of life needs. Kujang comes from Kudi Hyang. Kudi is functionally a farming tool that is prepared to honor and worship Hyang, the supreme ruler of the universe. The concept of Kujang is far from the utility function of a tool or a weapon. Kujang is a symbolic artifact that functions intrinsically, and not a weapon, because planning from the beginning can be distinguished by making weapons. Then Kujang in form follows function proven not to fulfill utility requirement. Kujang which is identified with the term